Improving Organizational Citizenship Behavior Through Buddhist Leadership in Student Activity Units in Higher Education - Virna Dita Pratiwi; Juni Suryanadi; Vike Aprilianin Marwintaria Saputri; Hendra Ardianto; Komang Sutawan; Candra Kusuma (International Journal of Science and Applied Science: Conference Series, 2024)
Higher education shapes students' skills, character, and morals, including participation in student organizations such as Buddhist UKM. However, Buddhist UKM at Bandar Lampung City College faces challenges, such as low member participation and ineffective leadership. This research investigates the effect of Buddhist leadership towards the Organizational Citizenship Behavior (OCB) and its implications for Buddhist student organizations (UKM). This study approach and method developed with a quantitative and survey. The instrument in the research used a questionnaire. The population was 308 respondents in total, and as many as 175 respondents were used as samples taken using the Slovin formula. The analysis test in  research used path analysis. This study shows a significant favorable influence between Buddhist leadership and (OCB). It means that the better the Buddha's leadership motivates members to contribute voluntarily and actively to the organization's activities, further enhancing OCB, which plays a role in organization to achive the success and effectiveness.